Eating disorders and competitive sports - Platen, P. (Handbook of eating disorders and obesity, 2024)
Given the huge importance of physical activity for health, all people should regularly engage in physical activity. However, sometimes, athletic activity can be associated with an increased health risk. This includes an under-caloric diet, which can affect the entire range of eating disorders up to classical eating disorders. In those sports where there is high pressure for a lean physique, there is an increased risk for the occurrence of eating disorders up to clinically manifest eating disorders. An insufficient energy intake from food and/or an excessive energy expenditure through competitive sports training with or without manifest eating disorders, as well as a hypothalamic-induced reduction of sex hormones and decreased bone density, have significant health consequences for the affected athletes. Therefore, preventive and therapeutic measures should be consistently applied, especially in high-risk sports.